2017
DOI: 10.1039/c7tc00454k
|View full text |Cite
|
Sign up to set email alerts
|

Patterning and fluorescence tuning of quantum dots with haptic-interfaced bubble printing

Abstract: Semiconductor quantum dots (QDs) are attractive for a wide range of applications such as displays, light-emitting devices, and sensors due to their properties such as tunable fluorescence wavelength, high brightness, and narrow bandwidth. Most of the applications require precise patterning of QDs with targeted properties on solid-state substrates. Herein, we have developed a haptic-interfaced bubble printing (HIBP) technique to enable high-resolution (510 nm) high-throughput (>104 μm s−1) patterning of QDs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…(h) Haptic interface for bubble printing at different downscaling factors. 35 Adapted with permission from ref 35. Copyright 2017 The Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…(h) Haptic interface for bubble printing at different downscaling factors. 35 Adapted with permission from ref 35. Copyright 2017 The Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…Metals, polymers, organic molecules 10 mm s −1 [68] ≈510 nm [71] -50 µm [77] I) Laser modulation enables the formation of continuous patterns. [69] II) 3D hollow spherical structures covered with particles were demonstrated.…”
Section: Photothermal Printingmentioning
confidence: 99%
“…manner of material fixation to the substrate, which makes it appealing for the assembly of a wide range of materials. It was referred to in the literature by many names: bubble printing, [32,68] laser-induced microbubble technique (LIMBT), [69,70] hapticinterfaced bubble printing, [71] bubble pen lithography, [72] laserinduced micro-nano bubble, [73] continuous-wave laser-induced vapor bubble, [74] optothermally generated surface bubble, [75,76] thermo-optically manipulated laser-induced microbubbles, [77,78] and optothermal-surface bubble-assisted printing. [79] Mechanism: Thermal heating arises from a CW laser beam that is absorbed by the preformed dispersed particles or a light absorbing substrate.…”
Section: Thermally Driven Reactionsmentioning
confidence: 99%
“…[ 93–95 ] Along with surface assembly of microbes, synthetic particles, and molecules, small‐molecule sensing has been reported based on this phenomenon. [ 96–105 ] However, a high working temperature required to vaporize water has prevented the optothermally generated microbubbles from being applied to sensing proteins, whose activity is subject to thermal denaturation. [ 95,106 ] Kim et al.…”
Section: Diffusion‐limit‐breaking Systems For Enhancing Sensor–analytmentioning
confidence: 99%
“…[93][94][95] Along with surface assembly of microbes, synthetic particles, and molecules, small-molecule sensing has been reported based on this phenomenon. [96][97][98][99][100][101][102][103][104][105] However, a high working temperature required to vaporize water has prevented the optothermally generated microbubbles from being applied to sensing proteins, whose activity is subject to thermal denaturation. [95,106] Kim et al reported a biphasic liquid system wherein volatile, water-immiscible perfluoropentane (PFP) was emulsified into an aqueous medium as a bubble-generating liquid (Figure 5e).…”
Section: Enhanced Analyte-sensor Contact By Analyte Concentratingmentioning
confidence: 99%